2003
DOI: 10.1038/sj.npp.1300231
|View full text |Cite
|
Sign up to set email alerts
|

Lower CSF Homovanillic Acid Levels in Depressed Patients with a History of Alcoholism

Abstract: Major depression and alcoholism are often comorbid, resulting in more impairment and more suicidal behavior compared with either diagnosis alone. This study compared clinical features and cerebrospinal fluid (CSF) monoamine metabolites in depressed subjects with and without a history of alcoholism and healthy volunteers. We hypothesized that depressed subjects with a history of alcoholism would be more aggressive, impulsive, and suicidal than depressed subjects without a history of alcoholism, and would have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 103 publications
(117 reference statements)
1
25
0
Order By: Relevance
“…For example, we have demonstrated that in individuals with major depression, those with comorbid alcoholism had lower CSF homovanillic acid (HVA) levels compared with those without comorbid alcoholism (Sher et al, 2003). However, our study did not focus on suicidal behavior.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, we have demonstrated that in individuals with major depression, those with comorbid alcoholism had lower CSF homovanillic acid (HVA) levels compared with those without comorbid alcoholism (Sher et al, 2003). However, our study did not focus on suicidal behavior.…”
Section: Introductionmentioning
confidence: 80%
“…Alcoholism is associated with altered CSF monoamine metabolite levels (Ballenger et al, 1979;Banki and Molnar, 1981;Borg et al, 1985;Ratsma et al, 2002;Sher et al, 2003). For example, we have demonstrated that in individuals with major depression, those with comorbid alcoholism had lower CSF homovanillic acid (HVA) levels compared with those without comorbid alcoholism (Sher et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the intricate relationships and the causal links between alcohol abuse and/or dependence, personality traits and suicidal behavior are not clearly understood and still a matter of debate, impulsive and aggressive traits are probably key common predisposing factors [Koller et al, 2002;Sher et al, 2003;Conner and Duberstein, 2004].…”
Section: Comorbid Psychiatric-personality Disorders and Suicidal Behamentioning
confidence: 99%
“…Levels of HVA have been related to aggressive behavior, wounding, sexual behavior, and social dominance in vervets and macaques (12,(20)(21)(22)(23). Numerous studies suggest associations between CSF MA metabolite concentrations and various human behavioral disorders (15,24,25), but other than relationships of CSF 5-HIAA to suicidal and aggressive behaviors (26), these associations remain mostly equivocal and nonreplicated, in part because of the difficulty in obtaining CSF from sufficient human subjects. In addition, human studies, in contrast to those in NHPs, rely on lumbar CSF, which may less accurately reflect brain MA levels than cisternal CSF (27).…”
mentioning
confidence: 99%